PELATIHAN MODUL AJAR BERDIFERENSIASI DI SEKOLAH INKLUSIF : PELATIHAN MODUL AJAR BERDIFERENSIASI DI SEKOLAH INKLUSIF - Wicaksono, Vicky Dwi; Muhimmah, Hitta Alfi; Sukartiningsih, Wahyu; Julianto; Mulyani; Dellarosa, Maretha (Universitas Negeri Surabaya, 2025)
The differentiated instruction approach is one of the strategies aimed at creating inclusive learning. This training for creating differentiated teaching modules is designed for elementary school teachers as an effort to create innovative and relevant inclusive schools in the era of the Industrial Revolution 4.0. Differentiated teaching modules are collections of learning modules developed to accommodate students' diverse learning needs. Therefore, it is crucial for teachers to understand how to design these modules to achieve effective and enjoyable learning for students. This training explores the use of differentiated teaching modules as an effective teaching tool, enabling teachers to create engaging, interactive, and student-centered learning materials. The methods used in this training include lectures, Q&A sessions, discussions, assignments, and independent practice. The results of this training indicate that 98% of teachers feel supported by the training in creating differentiated teaching modules, which aids in the growth and development of students. Keywords:Teaching Modules, Differentiation, Inclusive School